2022
DOI: 10.1101/lm.053597.122
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hormonal contraceptives on sex differences in fear conditioning and fear extinction in PTSD

Abstract: Sex differences in the neurobiological mechanisms involved in fear conditioning and extinction have been suggested to contribute to differential vulnerability for the development of posttraumatic stress disorder (PTSD) in women compared with men. Reproductive hormones, such as estradiol, have been shown to facilitate fear conditioning and extinction learning and may explain some of these differences. However, the effect of commonly used hormonal contraceptives on the neurobiological mechanisms of fear conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…A negative relationship between salivary estradiol levels and the number of reported PTSD symptoms has been reported in a sample of trauma-exposed women, such that more estradiol was associated with less PTSD symptoms [50]. Exogenous estrogen administration in the form of birth control (synthetic estradiol) has been successfully utilized in order to increase the efficacy of extinction training (which has implications for exposure therapies) in women with PTSD [51]. Naturally occurring low estrogen levels seem to impair extinction learning among women with PTSD [52, 53].…”
Section: Resultsmentioning
confidence: 99%
“…A negative relationship between salivary estradiol levels and the number of reported PTSD symptoms has been reported in a sample of trauma-exposed women, such that more estradiol was associated with less PTSD symptoms [50]. Exogenous estrogen administration in the form of birth control (synthetic estradiol) has been successfully utilized in order to increase the efficacy of extinction training (which has implications for exposure therapies) in women with PTSD [51]. Naturally occurring low estrogen levels seem to impair extinction learning among women with PTSD [52, 53].…”
Section: Resultsmentioning
confidence: 99%
“…Women in the low estradiol group did not display either discrimination or inhibition when measured via FPS. A study by Bartholomew and colleagues utilized a trauma-exposed sample and found that women on hormonal contraceptives (low levels of ovarian hormones but higher synthetic hormones) demonstrated a faster time course of fear learning when compared to naturally cycling women who were in the early follicular phase of their menstrual cycle (low estradiol and progesterone) and men [ 42 ]. This study is unique in its comparison of women on hormonal contraceptives and women with low endogenous estradiol and suggest there may be some enhancements in fear acquisition specifically due to synthetic hormones.…”
Section: Gonadal Hormone Effects In Clinical Samplesmentioning
confidence: 99%
“…There were no differences in extinction based on PTSD diagnosis among those with high estradiol [ 44 ]. The afore-mentioned Bartholomew study that compared trauma-exposed women on hormonal contraceptives and women in the follicular phase of the menstrual cycle extinguished the previously conditioned fear 72 h after acquisition and found that women on hormonal contraceptives displayed a faster time course of extinction learning suggesting that synthetic hormones from hormonal contraceptives might be impacting both acquisition and extinction learning [ 42 ]. The results with fear acquisition, inhibition, and extinction in clinical samples contrasts with the lack of evidence for any hormonal impact on fear acquisition and extinction seen in community samples.…”
Section: Gonadal Hormone Effects In Clinical Samplesmentioning
confidence: 99%
See 2 more Smart Citations